Peran Humas dalam Meningkatkan Citra Positif Madrasah melalui Media dan Publisitas di MTS Fathur Rahman Sukorambi Jember - Khoirumansyah Khoirumansyah; Karlinda Anna Mudrikah; Irmatus Sa’adah; Holifatul Hasanah; Rofiq Hidayat (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This research was conducted based on the importance of the image of educational institutions in gaining public trust, making the role of Public Relations (PR) as a public communication manager highly essential. MTs Fathur Rahman Sukorambi Jember was chosen as the research site because the institution is currently striving to enhance its positive image through the optimization of media and sustainable publicity strategies. The aim of this study is to describe the role of PR in building the image of the madrasah, as well as to analyze the communication strategies employed, the forms of publicity implemented, and the challenges faced in its execution.This research applies a qualitative approach with a field research design. Informants were selected through purposive sampling, involving parties considered relevant and knowledgeable about public relations activities, such as the head of the madrasah, PR staff, teachers, students, and parents’ representatives. Data were collected through observations of madrasah activities, in-depth interviews, and documentation in the form of archives and published media. The data were analyzed descriptively, emphasizing the researcher’s interpretation of communication patterns, publicity strategies, and their impact on public perception of the madrasah’s image.The findings reveal that PR functions as a communicator, mediator, and builder of a positive madrasah image. The use of conventional media and digital platforms such as Facebook, Instagram, and WhatsApp Groups has proven effective in reaching a wider community and enhancing public interaction. Documentation of academic and non-academic activities also strengthens the legitimacy of the institution’s achievements. The main obstacles encountered include limited human resources, technological facilities, and consistency in information management. Nevertheless, overall, the role of PR has been proven significant in improving the positive image of MTs Fathur Rahman Sukorambi Jember.